Clear Corneal Phacovitrectomy with Posterior Capsulorhexis and IOL Implantation in Management of Selective Vitreoretinal Cases - Ernest V. Boiko; Sergey V. Churashov; Alexei N. Kulikov; Dmitrii S. Maltsev (Journal of Ophthalmology)
Purpose. To describe our technique, clear corneal phacovitrectomy with posterior capsulorhexis (CCPV), for the management of selected posterior segment intraocular foreign body (IOFB), posteriorly dislocated lens fragments (PDLF), and proliferative diabetic retinopathy (PDR) cases. Methods. This was a single-center retrospective interventional case series. In 21 patients (21 eyes) we performed phacovitrectomy through three clear corneal tunnel incisions (CCTI) and posterior capsulorhexis to remove IOFB (n=8), PDLF from the vitreous cavity after complicated phacoemulsification (n=6), and vitreous hemorrhage and epiretinal membranes in PDR (n=7). The procedure was completed with implantation of a hydrophobic acrylic IOL through the CCTI. Results. The mean visual acuity (logMAR) was 0.90 preoperative and improved to 0.26 over a mean follow-up of 8.7 months (range, 6–12 months). The intraocular lens was implanted into the capsular bag (n=12) or onto the anterior capsule (n=9). One PDR patient experienced an intraprocedural complication, hemorrhage from isolated fibrovascular adhesions. One IOFB patient developed apparent anterior proliferative vitreoretinopathy and required a repeat intervention. Conclusion. Selected vitreoretinal IOFB, PDLF, and PDR cases can be successfully managed by a combined surgical approach involving clear corneal phacovitrectomy with posterior capsulorhexis and implantation of an IOL, with good visual outcome and a low complication rate.